Can heat therapy help patients with heart failure?. Issue 7 (8th March 2020) - Ye, Winnie N.; Thipse, Madhura; Mahdi, Maleka Ben; Azad, Sharlin; Davies, Ross; Ruel, Marc; Silver, Marc A.; Hakami, Lale; Mesana, Thierry; Leenen, Frans; Mussivand, Tofy
Abstract: To review and analyze the clinical outcomes of thermal therapy (≤1.4°C increase in core body temperature) in patients with heart failure (HF). A systematic review and meta‐analysis regarding the effects of thermal therapy on HF was done by searching PubMed, Ovid Medline, Ovid Embase, Scopus, and internal databases up to date (2019). Improvement in the New York Heart Association (NYHA) class : Ten studies with 310 patients showed significant improvement in NYHA class. Only 7 among 40 patients remained in Class IV and 99 patients in Class III from 155 patients. Increased patients in lower classes indicate that more patients showed improvement. Sixteen studies on 506 patients showed an overall improvement of 4.4% of left ventricular ejection fraction (LVEF). Four studies reported improved endothelial dysfunction by 1.7% increase in flow‐mediated dilation (FMD) on 130 patients. Reduction in blood pressure: Thermal therapy reduced both systolic blood pressure (SBP) and diastolic blood pressure by 3.1% and 5.31%, respectively, in 431 patients of 15 studies. Decrease in cardiothoracic ratio (CTR): Eight studies reported an average of 5.55% reduction of CTR in a total of 347 patients. Improvement in oxidative stress markers: Plasma brain natriuretic peptide (BNP) levels significantly decreased (mean difference of 14.8 pg/dL) in 303 patients of 9 studies. Improvement of quality of life: Among 65 patients, thermal therapy reduced cardiac death and rehospitalization by 31.3%. A slight increase in core body temperature is a promising, noninvasive, effective, and complementary therapy for patients with HF. Further clinical studies are recommended.